Effects of slightly acidic electrolyzed water on the quality and antioxidant capacity of fresh red waxy corn during postharvest cold storage - Wang, Chunfang; Liu, Hongru; Liu, Chenxia; Wei, Yuzhen; Wang, Juanzi; Zhang, Yi; Wang, Xiao; Chen, Bingjie; Yan, Weiqiang; Qiao, Yongjin (Frontiers in Plant Science, 2024)
Fresh red waxy corn was consumed worldwide for its unique flavor and enriched nutrients, but it was susceptible to deterioration with a short shelf-life. This study explored the effect of slightly acidic electrolyzed water (SAEW) treatment on the quality and antioxidant capacity of fresh red waxy corn during postharvest cold storage up to 40 d. The SAEW treatment exhibited lower weight loss, softer firmness, while higher TSS and moisture content than the control group. Correspondingly, the SAEW maintained the microstructure of endosperm cell wall and starch granules of fresh red waxy corn kernels well, contributing to the good sensory quality. Further, the SAEW effectively reduced the accumulation of H2O2 content, elevated the O2 -• scavenging ability and maintained higher CAT and APX activities, decreased the decline of the flavonoids and anthocyanin during the storage. These results revealed that SAEW treatment could be a promising preservation method to maintain higher quality attributes and antioxidant capacity of fresh red waxy corn during postharvest cold storage.